ANALISA PENGARUH PROMOSI, INFLUENCER DAN BRAND AMBASSADOR TERHADAP MINAT BELI PRODUK SKINCARE SKINTIFIC DI MEDIA SOSIAL TIKTOK - Albiansyah, Albiansyah; Indah Hanna , Ameylia (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This study aims to analyze the influence of promotions, influencers, and brand ambassadors on purchase intention for Skintific skincare products. This study used a quantitative method, collecting data through a questionnaire distributed to 100 respondents who are Skintific product users. The analysis results using Statistical Product and Service Solutions (SPSS) showed a multiple linear regression coefficient of Y = 7.421 -5.741X1 + 5.931X2 + 0.662X3 and an adjusted R-squared value of 0.729, or 72.9%. The t-test values for X1 = 0.024, X2 = 0.019, and X3 = 0.000. The independent variables in this study were Promotion (X1), Influencer (X2), and Brand Ambassador (X3), while the dependent variable was Purchase Intention (Y). From the results of the t-test analysis with a significance level of 5% shows that Promotion has a significant negative influence on purchasing interest, with a t-count value of -5.759 and a significance of 0.024 (0.024 <0.05), influencers show a significant positive influence on purchasing interest, with a t-count value of 5.996 and a significance of 0.019 (0.019 <0.05), Brand Ambassador has a significant positive influence on purchasing interest, with a t-count value of 0.650 and a significance of 0.000 (0.000 <0.05). The results of the F test show that simultaneously or simultaneously the promotion variable and brand ambassador have an influence on purchasing interest. With an F-count value of 89.567 with a significance level of 0.000 (0.000 <0.05). This calculated F-value is much larger than the F-table value of 2.70 at degrees of freedom (df) 3 and 96. It can be concluded that there is a significant simultaneous influence between promotion, influencers, and brand ambassadors on product purchase interest.